Sudro Hakimi's Political Strategy in Winning the 2019 Interim Mayoral Election in Nagari Talu - Riko Riyanda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
This research aims to describe and identify Sudro Hakimi's political strategy in winning the Inter-Time Wali Nagari electionin Talu. In this study it was found that Sudro Hakimi's political strategy was effective in winning him over as wali nagari over time. The strategy used is offensive by strengthening the electoral base and expanding the network of voters (musyna participants) by visiting ninik mamak in villages with priority areas where there are no candidates. Then by using a defensive strategy, namely by keeping voters who are already committed to expressing their support and choice to Sudro Hakimi. The next strategy is a campaign carried out by means of direct friendship to voters by Sudro Hakimi in areas where there are no candidates and friendship by the winning team in areas where the opposing team is based.